A Novel Frameshift Mutation at Codons 138/139 (HBB: c.417_418insT) on the β-Globin Gene Leads to β-Thalassemia - Jiang, Fan; Huang, Lv-Yin; Chen, Gui-Lan; Zhou, Jian-Ying; Xie, Xing-Mei; Li, Dong-Zhi (Hemoglobin, 2017)
We describe a new β-thalassemic mutation in a Chinese subject. This allele develops by insertion of one nucleotide (+T) between codons 138 and 139 in the third exon of the β-globin gene. The mutation causes a frameshift that leads to a termination codon at codon 139. In the heterozygote, this allele has the phenotype of classical β-thalassemia (β-thal) minor.